Trichoderma and Nanotechnology in Sustainable Agriculture: A Review - Ramírez-Valdespino, Claudia A.; Orrantia-Borunda, Erasmo (Frontiers in Fungal Biology, 2021)
Due to their unique properties and functionalities, nanomaterials can be found in different activities as pharmaceutics, cosmetics, medicine, and agriculture, among others. Nowadays, formulations with nano compounds exist to reduce the application of conventional pesticides and fertilizers. Among the most used are nanoparticles (NPs) of copper, zinc, or silver, which are known because of their cytotoxicity, and their accumulation can change the dynamic of microbes present in the soil. In agriculture, Trichoderma is widely utilized as a safe biocontrol strategy and to promote plant yield, making it susceptible to be in contact with nanomaterials that can interfere with its viability as well as its biocontrol and plant growth promotion effects. It is well-known that strains of Trichoderma can tolerate and uptake heavy metals in their bulk form, but it is poorly understood whether the same occurs with nanomaterials. Interestingly, Trichoderma can synthesize NPs that exhibit antimicrobial activities against various organisms of interest, including plant pathogens. In this study, we summarize the main findings regarding Trichoderma and nanotechnology, including its use to synthesize NPs and the consequence that these compounds might have in this fungus and its associations. Moreover, based on these findings we discuss whether it is feasible to develop agrochemicals that combine NPs and Trichoderma strains to generate more sustainable products or not.